Immigration Services For Indonesian Migrant Workers During The Covid-19 Pandemic - Yokhebed Arumdika Probosambodo; Widiastuti (International Journal Of Community Service, 2022)
This study aims to determine the immigration services provided by the Indonesian government for Indonesian Migrant Workers during the COVID-19 pandemic. The method used in this research is normative legal research. Normative legal research is research conducted by reviewing the applicable laws and regulations on a particular legal issue. The COVID-19pandemic has become a separate obstacle for Indonesian Migrant Workers. This is because of the policies and/or restrictions implemented in order to break the chain of COVID-19 which actually makes their fate seem adrift, for example: Indonesian Migrant Workers trapped in receiving countries, Migrant Workers Problematic Indonesia, the travel ban and lockdown policies implemented by several countries in the world, not a few of which are the destination countries for the majority of Indonesian Migrant Workers, such as Saudi Arabia, Taiwan, Hong Kong, and others. In facing this challenge, the Government of Indonesia does not remain silent. The government through the Directorate General of Immigration of the Ministry of Law and Human Rights issues policies in providing protection and services for Indonesian Migrant Workers during the COVID-19 pandemic.